Comparison of Adenoma Detection Rates in Afro-Caribbeans and Non-Hispanic Whites Undergoing First Screening Colonoscopy. Issue 5 (May 2016) - Alvarez, Alicia; Tandon, Kanwarpreet; To, Chau; Imam, Mohamad; Shah, Kinchit; Hakim, Seifeldin; Amer, Hassan; Estrada, Jose; Jimenez, Brenda; Castro, Fernando J.
Abstract : Objectives: The African American population has a higher prevalence of advanced colon adenomas when compared with non-Hispanic whites and Hispanics, but the risk in other black populations has not been evaluated. Although the Afro-Caribbean population is a significant demographic segment in some regions of the United States, the data are limited on the prevalence of colon adenomas in this group and there is no comparison with a non-Hispanic white population. The objective of our study was to compare the prevalence of adenomas in Afro-Caribbean versus non-Hispanic white populations. Methods: A total of 880 Afro-Caribbean patients and 1828 non-Hispanic white patients undergoing their first screening colonoscopy between January 2008 and August 2014 was included in the study. Results: A total of 2708 patients met entry criteria for the study. The adenoma detection rate among Afro-Caribbeans was 29% and 31% among non-Hispanic whites. There was no statistically significant difference in the prevalence of adenomas in the two groups ( P = 0.28), and the rate of advanced adenomas also was similar in both groups (8.6% in Afro-Caribbeans, 9.2% in non-Hispanic whites; P = 0.60). A multivariate analysis also found no difference in the occurrence of adenomas ( P = 0.60) or advanced adenomas ( P = 0.99) between Afro-Caribbeans and non-Hispanic whites. Conclusions: We found a similar adenoma detection rate and advanced adenoma prevalence among Afro-Caribbeans and non-Hispanic whites undergoing their first screening colonoscopy. As such, the Afro-Caribbean population may not have the same risk of colorectal neoplasia as what has been described for African Americans. Based on these results, it is appropriate to initiate colorectal cancer screening for Afro-Caribbeans at age 50 as recommended for non-Hispanic whites. Abstract : Despite the higher risk of colorectal neoplasia in African Americans in the United States and recommendations for earlier screening, the risk in subgroups of the African American population has not been studied. The authors have evaluated the risk of colorectal neoplasia in the Afro-Caribbean population in comparison with the non-Hispanic white population.